CULTURAL INFLUENCE ON THE TRANSLATION OF ‘ECLIPSE’ NOVEL BY STEPHENIE MEYER: A SEMIOTIC PERSPECTIVE - Sesilia Seli, (Fonseca, Journal of Communication, 2024)
Translating English literature into Indonesian faces challenges related to cultural nuances. This study investigates the impact of cultural influence on the translation of Stephenie Meyer’s novel Eclipse. Employing a qualitative method and a semiotic approach to translation, the research analyzes 30 data points selected through purposive sampling from the novel and its Indonesian translation. The objective of the translation is to convey the ‘Eclipse’ story faithfully to the target language (TL) readers, particularly adults. The translator introduces the TL audience to the source language (SL) culture. The findings reveal that (1) the use of cultural index by the translator as a means to preserve the source culture significantly influences the TL. Some translations face challenges in being accepted in the target language due to the unavailability of certain meanings in Indonesian, while others are accepted with equivalence that corresponds to the SL; (2) to address cultural translation challenges, the translator employs transference and naturalization procedures, with 87% predominantly using transference and 13% using naturalization. However, some of these procedures prove inaccurate in the TL due to a lack of corresponding elements. This study provides insights for translators to navigate cultural challenges in translating between languages with distinct cultural backgrounds. Furthermore, it serves as a reference for understanding how the myth as an ideology can be employed in analyzing the culture of a specific society.